typos calcul mental
authorDenise sur Lya <sekhmet@lya>
Sat, 26 Mar 2016 13:51:18 +0000 (14:51 +0100)
committerDenise sur Lya <sekhmet@lya>
Sat, 26 Mar 2016 13:51:18 +0000 (14:51 +0100)
1ere/calcul_mental/derivee2.pdf
1ere/calcul_mental/derivee2.tex
2nde/calcul_mental/facto.pdf
2nde/calcul_mental/facto.tex

index 0721c3d..3bb2ace 100644 (file)
Binary files a/1ere/calcul_mental/derivee2.pdf and b/1ere/calcul_mental/derivee2.pdf differ
index 0d444cd..f4e91ff 100644 (file)
@@ -13,7 +13,7 @@
 \newcommand\qd{$f(x) = x^2 + x + 1$}
 \newcommand\rd{$f'(x) = 2x + 1$}
 \newcommand\qe{$f(x) = 3x^3 + 2x^2 + x + \sqrt 2$}
-\newcommand\re{$f'(x) = 9x^2 + 4x$}
+\newcommand\re{$f'(x) = 9x^2 + 4x + 1$}
 
 %%%%%%%%%%%%%%%
 
index c53c908..57e83ce 100644 (file)
Binary files a/2nde/calcul_mental/facto.pdf and b/2nde/calcul_mental/facto.pdf differ
index 179acc3..5622ede 100644 (file)
@@ -35,7 +35,7 @@ E(x) = x^2(x-4) - 8x(x-4) + x-4
 \slide{
 \begin{enumerate}
 \item $A(x) = x^2 + 3x$ \reponse{2}{$A(x) = x(x+3)$}
-\item $B(y) =  y^2 -36$ \reponse{3}{$B(y) = (x+6)(y-6)$}
+\item $B(y) =  y^2 -36$ \reponse{3}{$B(y) = (y+6)(y-6)$}
 \item $C(x) = x^2 -6x + 9$ \reponse{4}{$C(x) = (x-3)^2$}
 \item $D(t) = t(t+4) -8(t+4)$ \reponse{5}{$D(t) =(t+4)(t-8) $}
 \item $E(x) = x^2(x-4) - 8x(x-4) + x-4$ \reponse{6}{$E(x) = (x-4)(x^2 -8x + 1)$}